The complexity of non-violence action (2016)
This chapter claims that non-violent action corresponds to a political dimension in which society has become a magnificent complex organism. Moreover, non-violent action corresponds to the phase of highest complexity in a social organization. Examples are provided ranging from ecology to population biology, from ethology to swarm intelligence. At the end, several conclusions are drawn that shed new lights on the social, cultural, and political understanding of our world and to the foreseeable future. The study of non-violent action provides sufficient arguments that allow the distinction between 'politics' and 'policy', i.e. 'policies', so much so that politics is highlighted as a highest and most significant dimension of the human experience, and policies are then considered as secondary or lower. The human rights provide the ground for the understanding and comprehension of non-violent actions. In the core of the text a topology of non-violent actions is provided along with its explanation. © 2017, IGI Global. All rights reserved.